OGEE v2: an update of the online gene essentiality database with special focus on differentially essential genes in human cancer cell lines - Chen, Wei-Hua; Bork, Peer (Nucleic acids symposium series, 2017)
Abstract. OGEE is an Online GEne Essentiality database. To enhance our understanding of the essentiality of genes, in OGEE we collected experimentally tested e
Gesehen am 29.06.2018
Published online 30 October 2016